Use of an ultraviolet tracer in simulation training for the clinical management of Ebola virus disease. Issue 3 (November 2015) - Clay, K.A.; O'Shea, M.K.; Fletcher, T.; Moore, A.J.; Burns, D.S.; Craig, D.; Adam, M.; Johnston, A.M.; Bailey, M.S.; Gibson, C.
Summary In October 2014 the UK military deployed to Sierra Leone to provide care for healthcare workers affected by Ebola virus disease. A training package designed by the Army Medical Services Training Centre prepared the deploying personnel in the required infection prevention and control measures. The training used ultraviolet tracer to provide validation of the skills required when treating patients with Ebola and to confirm subsequent decontamination. This training construct provided useful feedback to clinicians on their infection control measures and would be useful in the context of any infection spread by droplets and fomites.